EFFECT PRICE, LOCATION, SERVICE, AND STORE ATMOSPHERE ON PURCHASE DECISIONS AT COFFE SHOP HALUNA KOFFIE - Haifa Salsabila; Putu Nina Madiawati (SEAN Institute, 2023)
Haluna Koffie is one of the cafes located on Jl. Shutter No. 3 Bandung with a homie feel. Based on the level of consumption in Indonesia, it always increases every year, namely 249 thousand people in 2016 to 369 thousand people in 2021. Throughout 2021 there were fluctuations in sales decline of 48.2%. This phenomenon makes business people have to be able to create something different and are required to innovate in attracting consumers faster amid the increasingly fierce competition in the coffee shop business. This study aims to determine how much influence price, location, service, and store atmosphere have on purchasing decisions at HALUNA Koffie. The method used in this research is a quantitative method with descriptive and causal research types. This study used a sample of 100 respondents and data collection using a questionnaire method. The data analysis used is multiple linear regression. Based on the results of the study using descriptive analysis with the help of SPSS 25, it shows that price has a very good value with a score of 87.7%, location has a very good value with a score of 85.8%. service has a very good score of 89.6%, store atmosphere has a very good score with a score of 88.6%, and purchasing decisions have a very good score with a score of 88.2%. which simultaneously has a positive and significant effect on purchasing decisions